Free Rather Than Total Iron Content Is Critically Linked to the Fur Physiology in Shewanella oneidensis - Liu, Lulu; Feng, Xue; Wang, Wei; Chen, Yining; Chen, Zhe; Gao, Haichun (Frontiers in Microbiology, 2020)
Ferric uptake regulator (Fur) is a transcriptional regulator playing a central role in iron homeostasis of many bacteria and Fur inactivation commonly results in pleiotropic phenotypes. In Shewanella oneidensis, a representative of dissimilatory metal-reducing -proteobacteria capable of respiring a variety of chemicals as electron acceptors (EAs), the Fur loss substantially impairs respiration. However, to date the mechanism underlying the physiological phenomenon remains obscure. This investigation reveals that Fur loss compromises activity of iron proteins requiring biosynthetic processes for their iron cofactors, heme in particular. We then show that S. oneidensis Fur is critical for maintaining heme homeostasis by affecting both its biosynthesis and decomposition of the molecule. Intriguingly, the abundance of iron-containing proteins controlled by H2O2-responding regulator OxyR increases in the fur mutant because the Fur loss activates OxyR. By comparing suppression of membrane-impermeable, membrane-permeable, and intracellular-only iron chelators on heme deficiency and elevated H2O2 resistance, our data suggest that the elevation of the free iron content by the Fur loss is likely to be the predominant factor for the Fur physiology. Overall, these results provide circumstantial evidence that Fur inactivation disturbs bacterial iron homeostasis by altering transcription of its regulon members, through which many physiological processes, such as respiration and oxidative stress response, are transformed.